Preliminary study on the molecular features of mutation in multiple primary oral cancer by whole exome sequencing - Li, Kan; Gong, Jianbin; Zheng, Qiuhan; Yang, Le; Mei, Xueying; Chen, Jianghai; Liao, Guiqing; Liang, Yujie (Frontiers in Oncology, 2022)
Multiple primary cancers (MPC) refer to cancers that occur simultaneously or metachronously in the same individual. Incidence rate of MPC has increased recently, as survival time of malignant tumor patients has been greatly prolonged. From the clinical manifestations, it is hard to tell MPC from primary cancers (PC) in the same anatomical region. However, the biological behaviors seem to be distinct. Our study showed that the prognosis of multiple primary oral cancers (MP-OC) was worse than primary oral cancers (P-OC). In order to better understand the molecular mechanism of MP-OC, we used whole exon sequencing (WES) to analyze 9 patients with MP-OC and 21 patients with P-OC. The results showed that more somatic mutations were detected in MP-OC than in P-OC. MP-OC had more complicated mutation signatures, which were associated with age-related and APOBEC activity related signatures. Tumor mutational burden (TMB) and mutant-allele tumor heterogeneity (MATH) of MP-OC were insignificantly higher than those of P-OC. KEGG and GO analysis showed the different pathways of MP-OC and P-OC. In addition, MP-OC took amplification, not loss, as the main pattern of copy number variation (CNV), while P-OC took both. Lastly, we did not find significantly different mutant germline genes, but MSH-6 mutation may be a potential MP-OC driver. In short, our preliminary results showed MP-OC and P-OC had different molecular characteristics.